"Lwów Saved Us": Roma Survival in Lemberg 1941–44. Issue 3 (3rd July 2018) - Wawrzeniuk, Piotr
ABSTRACT: The ritualized memory of genocide has been a cornerstone of Roma political mobilization during at least the last three decades. A uniqueness paradigm has been developing for some time, applying a memorial discourse inspired by the Jewish Holocaust model. While paralleling each other in time, the mass murders of Jews and Roma during the Second World War differed on several points. In the General Government of the Occupied Polish Territories and the territories occupied by Nazi Germany after Operation Barbarossa, the persecution of Roma took place largely in local initiatives. Consequently, the Nazi policies varied considerably, leading to territories in which Roma were annihilated and those in which about half of the Roma population survived. Considerable differences could also appear within the same administrative unit. In Distrikt Galizien, the southeastern-most district of the General Government, Roma were persecuted violently in the countryside, while the district capital of Lemberg (Lwów, Lviv) saw a different course of events. The picture that appears from the available documents also diverges from survivor testimonies and general accounts of the persecution of Roma as being similar and parallel to that of Jews. Roma were present in Lemberg throughout the Nazi occupation and the authorities were aware of their whereabouts. Roma were not confined to the ghetto, but many, along with Poles and Ukrainians, remained within the territory of the ghetto, parts of which had constituted areas of Roma settlement in Lemberg since the mid nineteenth century. Several Roma also lived in wagons in various locations in 1942–43, as well as in quarters close to the town's centre. Altogether, several hundred Roma lived in Lemberg, and their treatment by the local courts was different from that of Jews, bearing more similarity to the way in which Polish and Ukrainian cases were handled.